2021
DOI: 10.1097/md.0000000000025390
|View full text |Cite
|
Sign up to set email alerts
|

The combined therapy of fecal microbiota transplantation and laxatives for functional constipation in adults

Abstract: Objective: Functional constipation is a prevalent, burdensome gastrointestinal disorder whose treatment remains challenging. Combined therapy uniting multiple treatments may be promising. Fecal microbiota transplantation (FMT) which tends to be an etiological treatment has been increasingly investigated in its management. Meanwhile, laxatives are widely used to relieve constipation temporarily, but their overall efficacy is poor. Therefore, we performed meta-analyses of randomized controlled trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Moreover, a recent meta‐analysis reported that probiotics which modify the gastrointestinal microbiota may improve whole gut transit time, stool frequency, and stool consistency 34 . Combined therapy comprising laxatives and fecal microbiota transplantation (FMT), where fecal material containing gut microbiota from a healthy individual is transplanted into a patient with a dysbiosis‐related disease or condition, 35 has been shown to be a reasonably effective and safe treatment for patients with functional constipation (risk ratio: 1.35; 95% CI: 1.14, 1.60; I2% = 13%) 36 . Therefore, it is possible that H .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent meta‐analysis reported that probiotics which modify the gastrointestinal microbiota may improve whole gut transit time, stool frequency, and stool consistency 34 . Combined therapy comprising laxatives and fecal microbiota transplantation (FMT), where fecal material containing gut microbiota from a healthy individual is transplanted into a patient with a dysbiosis‐related disease or condition, 35 has been shown to be a reasonably effective and safe treatment for patients with functional constipation (risk ratio: 1.35; 95% CI: 1.14, 1.60; I2% = 13%) 36 . Therefore, it is possible that H .…”
Section: Discussionmentioning
confidence: 99%
“…34 Combined therapy comprising laxatives and fecal microbiota transplantation (FMT), where fecal material containing gut microbiota from a healthy individual is transplanted into a patient with a dysbiosis-related disease or condition, 35 has been shown to be a reasonably effective and safe treatment for patients with functional constipation (risk ratio: 1.35; 95% CI: 1.14, 1.60; I2% = 13%). 36 Therefore, it is possible that H. pylori infection and its eradication treatment affect the profile of the gut microbiota and contribute to the abnormality and severity of bowel habits and symptoms.…”
Section: Association Of H Pylori Infection With Gut Microbiotamentioning
confidence: 99%
“…Considering the purpose of the present umbrella review, we selected those studies that included the largest number of RCTs. Ultimately, 7 meta-analyses met the eligibility criteria ( Hui et al., 2019 ; Ianiro et al., 2019 ; Caldeira et al., 2020 ; Proença et al., 2020 ; Tang et al., 2020 ; Dharmaratne et al., 2021 ; Fang et al., 2021 ). Figure 2 shows the flowchart of the literature search.…”
Section: Resultsmentioning
confidence: 99%
“…We used the GRADE (Grading of Recommendations, Assessment, Development and Evaluation) assessment to evaluate the credibility of the evidence provided by each association in the meta-analysis 27, 28 . Evidence from the meta-analysis of randomized controlled trials was evaluated based on the significance of the pooled effect, using a p value of <0.05 as statistical significance.…”
Section: Methodsmentioning
confidence: 99%